An efficient and practical aerobic oxidation of benzylic methylenes by recyclable N-hydroxyimide. Issue 5 (14th January 2021) - Wang, Jian; Zhang, Cheng; Ye, Xiao-Qing; Du, Wenting; Zeng, Shenxin; Xu, Jian-Hong; Yin, Hong
Abstract : An efficient and practical benzylic aerobic oxidation catalyzed by cheap and simple N -hydroxyimide organocatalyst has been achieved with high yields and broad substrate scope. Abstract : An efficient and practical benzylic aerobic oxidation catalyzed by cheap and simple N -hydroxyimide organocatalyst has been achieved with high yields and broad substrate scope. The organocatalyst used can be recycled and reused by simple workup and only minute amount (1 mol% in most cases) of simple iron salt is used as promoter. Phenyl substrates with mild and strong electron-withdrawing group could also be oxygenated in high yields as well as other benzylic methylenes. Influence of substituents, gram-scale application, catalysts decay and general mechanism of this methodology has also been discussed.